Valuasi Saham Perusahaan Menggunakan Metode Relative Valuation - Fredella Colline; Roseline Mannuela Anwar (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The data shows that the percentage of investors in Indonesia is very small, which is still below 1%, while the percentage of investors in neighboring countries is around 20% -30%. The purpose of this research is to help novice investors to see whether the company's stock price is undervalued or overalued and to compare the prediction accuracy of various ratios in the model. The ratios examined in this paper are Price Earning Ratio (PER), Price to Book Value (PBV), Price to Sales Ratio (PSR), and Price to cash flow from operation ratio (PCF). The approach used in this study is the Relative Valuation Method, where the value of an asset is calculated by looking at the market price for the same or similar asset. Of the 72 companies studied, 45 LQ 45 companies and the rest were peer companies in the same industrial sub-sector with LQ45 companies. Of the four ratios (PER, PBV, PSR and PCF), PCF gave the highest accuracy results. Based on the appropriate results of the four ratios, the OVERVALUED Shares (should be sold / not purchased): In 2018 there were 8 shares, in 2017 there were 12 shares and in 2016 there were 6 shares. UNDERVALUED Shares (preferably purchased / held): In 2018 there were 8 shares, in 2017 there were 5 shares, and in 2016 there were 11 shares. Keywords: Relative Valuation, Price/Earnings Ratio (PER), Price/Book Value (PBV), Price/Sales Ratio (PSR) dan Price to Cash Flow (PCF).